2018
DOI: 10.1186/s12940-018-0383-0
|View full text |Cite
|
Sign up to set email alerts
|

Early life swimming pool exposure and asthma onset in children – a case-control study

Abstract: BackgroundTrichloramine exposure in indoor swimming pools has been suggested to cause asthma in children. We aimed to investigate the risk of asthma onset among children in relation to individual trichloramine exposure.MethodsA longitudinal nested case-control study of 337 children with asthma (cases) and 633 controls aged 16–17 years was performed within a population-based cohort from The Obstructive Lung Disease in Northern Sweden studies (OLIN). Year of asthma onset and exposure time at different ages were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Ten air toxics in the combinations contained chlorine, three included heavy metal compounds, and many were acidic chemicals. This aligns with prior literature implicating acidic chemicals, chlorinated chemicals, and heavy metal compounds as risk factors for asthma and asthma severity (8,(41)(42)(43)(44). However, an understanding of the biological mechanisms through which these combinations of air toxics can jointly affect respiratory health and asthma merits further study.…”
Section: Discussionsupporting
confidence: 83%
“…Ten air toxics in the combinations contained chlorine, three included heavy metal compounds, and many were acidic chemicals. This aligns with prior literature implicating acidic chemicals, chlorinated chemicals, and heavy metal compounds as risk factors for asthma and asthma severity (8,(41)(42)(43)(44). However, an understanding of the biological mechanisms through which these combinations of air toxics can jointly affect respiratory health and asthma merits further study.…”
Section: Discussionsupporting
confidence: 83%
“…In another study, the same authors also reported the absence of any relationship between swimming attendance up to age 4 years and the development of hay fever symptoms at ages 7 and 10 years [11]. Andersson et al reported the absence of any relationship between a history of swimming before age 1 or 2 years and the development of wheeze by school-age [30]. The findings of these studies were thus in line with our own.…”
Section: Unadjusted or Adjusted Or A Multiple Imputation Or (95% Ci) supporting
confidence: 86%
“…43 Two studies in Sweden confirmed these observations while showing that the risk of allergic asthma correlated with the cumulative inhalation exposure to NCl 3 . 84,85 Associations between asthma and recreational swimming in chlorinated pools were also reported in Ireland, 86 Italy, 87 and Portugal. 88 Several other studies, however, provided no evidence of an increased asthma risk in recreational swimmers.…”
Section: Non-respiratory Symptomsmentioning
confidence: 85%
“…Important to note also that the risk of allergic asthma was more strongly linked to pool attendance during early childhood 43 . Two studies in Sweden confirmed these observations while showing that the risk of allergic asthma correlated with the cumulative inhalation exposure to NCl 3 84,85 …”
Section: Effects Of Chronic Exposuresmentioning
confidence: 89%